2017
DOI: 10.1021/acs.molpharmaceut.7b00118
|View full text |Cite
|
Sign up to set email alerts
|

PCPP-Adjuvanted Respiratory Syncytial Virus (RSV) sF Subunit Vaccine: Self-Assembled Supramolecular Complexes Enable Enhanced Immunogenicity and Protection

Abstract: PCPP, a well-defined polyphosphazene macromolecule, has been studied as an immunoadjuvant for a soluble form of the postfusion glycoprotein of respiratory syncytial virus (RSV sF), which is an attractive vaccine candidate for inducing RSV-specific immunity in mice and humans. We demonstrate that RSV sF-PCPP formulations induce high neutralization titers to RSV comparable to alum formulations even at a low PCPP dose and protect animals against viral challenge both in the lung and in the upper respiratory tract.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…After fusion with the host cell membrane, the F protein forms a stable post-fusion conformation. Previous reports indicate that pre-fusion conformation F protein is more suitable as an antigen than post-fusion conformation F protein, because it greatly induces neutralizing antibodies ( 5 , 10 , 11 ). In addition, most F proteins on formalin-inactivated RSV have post-fusion conformations ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…After fusion with the host cell membrane, the F protein forms a stable post-fusion conformation. Previous reports indicate that pre-fusion conformation F protein is more suitable as an antigen than post-fusion conformation F protein, because it greatly induces neutralizing antibodies ( 5 , 10 , 11 ). In addition, most F proteins on formalin-inactivated RSV have post-fusion conformations ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 One such study using PCPP for the adjuvantation of a soluble form of the postfusion RSV-F glycoprotein in mice indicated that PCPP could spontaneously self-assemble with the vaccine antigen, and enhance both T H 1 immune responses and protection from RSV challenge, in comparison to a standard aluminum adjuvant. 27 Another study using PCPP for the intranasal delivery into mice of a formalin-inactivated bovine RSV (FI-bRSV) vaccine combined with immunostimulatory CpG oligodeoxynucleotides indicated that the FI-bRSV /CpG/PCPP co-formulation could induce virus neutralizing antibody responses in the serum, IFN-Îł responses in the spleen and mucosal IgA responses in the lung, as well as protection from bRSV challenge. 28,29,30 These studies highlight the potential of such polyanionic adjuvants, which are also advantageous in terms of readiness of supply, easiness of formulation by simple mixing processes and quality control by using nuclear magnetic resonance (NMR) and high-performance size exclusion chromatography (HPSEC) techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvants are agents or drugs that have few or no antigenic effects or properties but can help enhance the efficacy and immunogenicity of vaccines (Mishra et al 2020 ). In many studies, several kinds of adjuvants were used that had significant effects on the immunogenicity of the vaccine (Cayatte et al 2017 ; Doener et al 2019 ; Gasparini et al 2001 ; Suschak et al 2017 ; Yang et al 2020 ). Adjuvants L7/L12 ribosomal protein (Behbahani 2020 ; Saadi et al 2017 ), beta-defensin (Gupta et al 2020 ; Wang et al 2020 ), HBHA protein (Kumar et al 2019 ; Lei et al 2020 ), and HBHA conserved sequence(Rashidian et al 2020 ; Solanki and Tiwari 2018 ) recently been identified as efficient and helpful adjuvants, and we used them in this study.…”
Section: Introductionmentioning
confidence: 99%